57 President Oral Presentation Pick: The exploration of blood microRNA profiling in feedlot cattle with different lameness phenotypes. (30th November 2020) - Li, Wentao; O'Hara, Eóin; Sun, Huizeng; Schwartzkopf-Genswein, Karen S; Guan, Leluo L
Abstract: Lameness is a significant economic and welfare issue in feedlot production. Effective treatment depends on diagnosing the cause of lameness accurately. There is increasing evidence that circulating microRNAs may serve as useful biomarkers for diagnosing disease. However, their association with lameness in feedlot cattle is currently unknown. The objective of this study was to investigate whether blood miRNA profiles can be associated with a specific lameness phenotype. Blood samples were collected via venepuncture (into Tempus™ Blood RNA Tubes) from 39 feedlot cattle diagnosed with digital dermatitis (DD; n = 2), toe tip necrosis syndrome (TTNS; n = 5), footrot (FR; n = 26) and healthy controls (HC; n = 6) for miRNA profiling using RNA sequencing. Samples were obtained at the time each animal was pulled from their pens for medical treatment. Total RNA was extracted from blood samples and subjected to small RNA libraries construction and RNA-sequencing. The sequence data analysis was performed using a web-based tool, sRNAtoolbox. A total of 596 miRNAs were identified across 39 blood samples with the expression of 444, 437, 465 and 575 miRNAs detected in the HC, DD, TTNS and FR groups, respectively. In addition, group-specific miRNAs were identified with 9 in the DD group, 45 in the TTN group, 28 in the FR group and 2 in the HC group. Moreover, 41, 8 and 36 differential expressed miRNAs (DE miRNAs) were detected in DD, TTNS and FR groups, respectively, when compared to the HC group using DeSeq2. These data suggest that miRNA profiles may differ according to lameness diagnosis in beef cattle. However, further investigation incorporating functional analyses of miRNA, increased sample size and the physiological profile of the animals are required to better understand the relationship between blood miRNA profiles and lameness in feedlot cattle.